DESIGN OF A TRANSMISSION INTENDED TO WHEELCHAIRS FOR DISABLED PEOPLE - Ionut GEONEA; Nicolae DUMITRU (Fiabilitate şi Durabilitate)
In this paper are presented the authors contributions on designing and evaluation of a mechanical transmission intended to be used to wheelchairs for disabled people. In most cases the wheelchairs propulsion system solution consist of two DC motors, mounted on wheels shafts directly, or by means an intermediary transmission with chains or belts. In this case the wheelchair must be equipped with a controller, generally based on a PWM technology. Proposed solution consists of a mechanical transmission based on differential gears, which uses two motors, for steering and for propulsion. For this design architecture the control solution is much simple and easy cost to design, consisting in one servo controller for two motors. Based on dimensional synthesis of transmission gears, is developed the design solution of the robotic wheelchair. The wheelchair motion simulation is studied in Adams software, for the case of traction, steering and combined motion. From Adams simulations are obtained the wheelchair motion trajectories, kinematic and dynamic parameters. Obtained results are analyzed and compared to other wheelchairs design solution, concluding that proposed design solution of this transmission can be successful used to a wheelchair experimental prototype.